(untitled) (Plant Bulletin, 2024)
A research study was led to estimate the genomic composition of five diverse forms of maize genotypes by investigating their combining abilities. The outcomes showed that General Combining Ability (GCA) in maize inbred lines exhibited significant variations across all characteristics under both heat and control environments. Specific Combining Ability (SCA) had significant variation in most characteristics under study, except for anthesis silk interval and number of ears per plant under heat stress. The genotypes ILC 276 and FM ILC 10 were recognized as decent general combiners for traits such as days to 50% tasseling, plant height, grain yield, number of kernels per ear, canopy temperature, cell membrane thermo-stability, pollen viability, and chlorophyll content. The crosses FM-ILC 10 x ILC 22, FM-ILC 10 x ILC 276, and FM-ILC 144 x ILC 255 were the best specific combiners for traits such as plant height, grain yield, number of kernels per ear, canopy temperature, pollen viability, and chlorophyll content. These hybrids are the best for high yield. The crosses ILC-22 x ILC-50, ILC-22 x ILC-276, ILC-50 x ILC-255, and ILC-50 x ILC-276 had high mid parent and better parent values for heterosis, demonstrating that they are the top-execution crosses with important positive heterosis for grain yield. Bi-plot investigation amid crosses of maize ILC 276 x ILC 22, ILC 276 x FM-ILC 10, and ILC 255 x FM-ILC 144 exhibited extreme genetic variability, and traits such as canopy temperature, cell membrane thermo-stability, plant height, anthesis silking interval and number of kernels per ear were positively associated with each other. Cluster analysis grouped the maize crosses into four and three clusters under normal and heat stress conditions respectively. These recognized crosses can be employed in further breeding plans to grow heat-tolerant hybrids for commercial seed production of maize.